1998
DOI: 10.1021/ja9808245
|View full text |Cite
|
Sign up to set email alerts
|

Structures of b and a Product Ions from the Fragmentation of Argentinated Peptides

Abstract: Argentinated (silver-containing) oligopeptides fragment under low-energy collision conditions to yield abundant argentinated product ions. The structures of the [b2 − H + Ag]+ and [a2 − H + Ag]+ ions have been determined by means of tandem mass spectrometry and confirmed by comparison with synthesized derivatives of the candidate [b2 − H + Ag]+ ion structure. The [b2 − H + Ag]+ ion was found to be an N-argentinated oxazolone, which could subsequently form the [a2 − H + Ag]+ ion and other product ions after col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 45 publications
3
55
0
Order By: Relevance
“…1 H NMR (400 MHz, CDCl 3 , 298 K) revealed ␦ 4.409 (s, 2H, NCH 2 CO), 7.473 (t, 2H, J ϭ 8.0 Hz, meta-H), 7.551 (t, 1H, J ϭ 6 Hz, para-H), and 7.977 (d, 2H, J ϭ 7.6 Hz, ortho-H). This spectrum is consistent with that previously published [47]. The ESI mass spectrum showed only the protonated molecule at m/z 162.…”
Section: Synthesis Of 2-phenyl-5-oxazolonesupporting
confidence: 92%
“…1 H NMR (400 MHz, CDCl 3 , 298 K) revealed ␦ 4.409 (s, 2H, NCH 2 CO), 7.473 (t, 2H, J ϭ 8.0 Hz, meta-H), 7.551 (t, 1H, J ϭ 6 Hz, para-H), and 7.977 (d, 2H, J ϭ 7.6 Hz, ortho-H). This spectrum is consistent with that previously published [47]. The ESI mass spectrum showed only the protonated molecule at m/z 162.…”
Section: Synthesis Of 2-phenyl-5-oxazolonesupporting
confidence: 92%
“…It has been shown that the formation of [b n ] C or the analogous [b n 1 C Cat] C ions involves the formation of a five-membered ring oxazolin-5-one structure, initiated by the attack on the carbonyl carbon atom of the amide bond being cleaved by an oxygen atom on a carbonyl moiety located to the N-terminal side of the reaction site. 12,20,21 For Ag C cationized GG or GA, there are no such carbonyl groups to serve as nucleophiles, and the attack to produce the [b 1 …”
Section: Ag]mentioning
confidence: 99%
“…Interactions of metal cations with peptides and proteins in gas‐phase complexes have been studied intensively,1–16 as reviewed 17. Of particular interest has been the use of gas‐phase peptide complex dissociations for structure elucidation of peptides by mass spectrometry 18.…”
Section: Introductionmentioning
confidence: 99%